Dampak Perkembangan Pasar Tanah Abang terhadap Dinamika Penggunaan Lahan di Kelurahan Kampung Bali dan Kebon Kacang, Jakarta: Analisis perkembangan pasar tanah abang serta perubahan penggunaan lahan tahun 2014 dan 2024 - Elnabi Permana (COMPACT: Spatial Development Journal, 2025)
The growth of trade and service activities at Tanah Abang Market has influenced land use changes in the urban villages of Kebon Kacang and Kampung Bali, Jakarta. Using a descriptive quantitative approach, the analysis draws on spatial data of land use from 2014 and 2024 through map overlay techniques and a scoring method applied to five market development sub-variables: number of commodities, market area, number of consumers, service coverage, and number of active kiosks and stalls. Findings categorize overall market development as moderate, with spatial impacts varying by proximity to the market center (100 m, 200 m, and 300 m). The 300-meter radius exhibits the most significant changes, including expanded commercial functions and intensified vertical development. In contrast, the 100 m and 200 m zones show limited changes due to space constraints and high density. These outcomes underscore the need for locally adaptive spatial planning in managing land use dynamics driven by large-scale traditional market growth in urban settings.